Analisis Faktor Risiko yang Berpengaruh terhadap Kejadian Plasenta Previa pada Ibu Bersalin - Silcia Sandra; Nur Indah Purnamasari; Saida Saida (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
According to WHO, 80% of maternal deaths are caused by heavy bleeding and cases of antepartum bleeding, especially placenta previa, based on WHO, show a percentage of 15% to 20% of maternal deaths. Placenta previa is a placenta that implants in the lower uterine segment so that it covers all or part of the internal uterine os. This study aims to determine whether maternal age, parity, history of SC, and history of abortion are risk factors that affect the incidence of placenta previa at Aliyah 2 General Hospital of Kendari City in 2021. This research is an observational analytic study with a case-control matching design. The population in this study were all mothers who gave birth at Aliyah 2 General Hospital of Kendari City for the period January 2019 to September 2021. Sampling used total sampling for the case group (diagnosed with placenta previa), while for the control group (undiagnosed with placenta previa) purposive sampling was used sampling. The number of samples was 80 mothers who gave birth, which consisted of 40 case samples and 40 control samples which had been matched in the form of the month and year of maternity. Data analysis was carried out by using the Statistical Program For Social Science (SPSS) statistical test using the Odds Ratio (OR). The test results showed that there was an effect between parity (OR 2.786 95% CI 1.125 – 6.899) and a history of abortion (OR 4.678 95% CI 1.193 – 18.337) with the incidence of placenta previa, and there was no effect between maternal age (OR 0.619 95% CI 0.235). – 1.627) and a history of SC (OR 0.848 95% CI 0.275 – 2.613) with the incidence of placenta previa at Aliyah 2 General Hospital of Kendari City in 2021. This study shows that parity and history of abortion are risk factors that affect the incidence of placenta previa, while maternal age and history of SC are not risk factors that affect the incidence of placenta previa at Aliyah 2 General Hospital of Kendari City in 2021.